Nestin expression associates with poor prognosis and triple negative phenotype in locally advanced (T4) breast cancer - F. Piras; M.T. Ionta; S. Lai; M.T. Perra; F. Atzori; L. Minerba; V. Pusceddu; C. Maxia; D. Murtas; P. Demurtas; B. Massidda; P. Sirigu (European Journal of Histochemistry, 2011)
Nestin, an intermediate filament protein, has traditionally been noted for its importance as a neural stem cell marker. However, in recent years, expression of nestin has shown to be associated with general proliferation of progenitor cell populations within neoplasms. There is no reported study addressing nestin expression in T4 breast cancer patients. Thus, the aim of the present study was to investigate, through immunohistochemistry, the expression and distribution of nestin in T4 breast cancer, in order to determine its association with clinical and pathological parameters as well as with patients’ outcome. Nestin was detectable in tumoral cells and in endothelial cells of blood microvessels, and it is significantly expressed in triple-negative and in inflammatory breast cancer (IBC) subgroups of T4 breast tumours. The Kaplan-Meier analysis showed that the presence of nestin in tumoral cells significantly predicted poor prognosis at 5-years survival (P=0.02) and with borderline significance at 10-years of survival (P=0.05) in T4 breast cancer patients. On the basis of these observations, we speculate that nestin expression may characterize tumours with an aggressive clinical behavior, suggesting that the presence of nestin in tumoral cells and vessels may be considered an important factor that leads to a poor prognosis. Further studies are awaited to define the biological role of nestin in the etiology of these subgroups of breast cancers.